Teachers’ Techniques in Providing Reading Material for Junior High School - Fujinda Kardila; Yetti Zainil (Journal of English Language Teaching, 2023)
This research was purposed to find out the technique that the teachers use in providing reading material and also their reasons why they choose that technique. This research was descriptive research. A total of 7 English teachers at junior high schools in sub-district of Lembang Jaya were chosen as the participants. Questionnaire, interview guideline, and document analysis were used as the instruments to collect the data. The questionnaire consisted of 20 close-ended questions related to the techniques of providing reading material. The interview guideline consisted 5 leading questions about the techniques of providing reading material and the reason why choosing that technique. According to the result of this study, 74% of English teachers a junior high school in sub-district of Lembang Jaya use adapting reading material technique in providing reading material for the students. The English teachers use 5 techniques of adapting reading material: modifying content, adding/deleting content, addressing omission, extending task, and reorganizing content. According to the further interview with the English teachers, there are three reasons why teachers adapt reading material: to help the students understand the reading material, to match the ability of the students, and to make the students interested to learn the material by making it more contextual. Even though the result of this research which was conducted in sub-district of Lembang Jaya is mostly all English teachers at junior high school use adapting reading material technique in providing reading material, this research was not purposed to generalize that result will be the same if the same research is conducted in other schools, area, and places.